2021
DOI: 10.1002/cpz1.119
|View full text |Cite
|
Sign up to set email alerts
|

Studying Sex Differences in Rodent Models of Addictive Behavior

Abstract: Animal models of addictive behaviors are useful for uncovering neural mechanisms involved in the development of dependence and for identifying risk factors for drug abuse. One such risk factor is biological sex, which strongly moderates drug self‐administration behavior in rodents. Female rodents are more likely to acquire drug self‐administration behaviors, consume higher amounts of drug, and reinstate drug‐seeking behavior more readily. Despite this female vulnerability, preclinical addiction research has la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 240 publications
(247 reference statements)
2
16
0
Order By: Relevance
“…There are sex differences in the role of the IL in renewal of appetitive Pavlovian conditioned responding (Anderson and Petrovich, 2018a,b). Sex differences in behavioral strategies could lead to differential effects of neural manipulations (Radke et al, 2021;Shansky and Murphy, 2021). We observe similar levels of renewal (Brown and Chaudhri, 2021) and reinstatement (LeCocq and Chaudhri, 2021) of appetitive Pavlovian conditioned responding in male and female rats.…”
Section: Discussionsupporting
confidence: 52%
“…There are sex differences in the role of the IL in renewal of appetitive Pavlovian conditioned responding (Anderson and Petrovich, 2018a,b). Sex differences in behavioral strategies could lead to differential effects of neural manipulations (Radke et al, 2021;Shansky and Murphy, 2021). We observe similar levels of renewal (Brown and Chaudhri, 2021) and reinstatement (LeCocq and Chaudhri, 2021) of appetitive Pavlovian conditioned responding in male and female rats.…”
Section: Discussionsupporting
confidence: 52%
“…If the interaction is significant, then a claim can be made that the sexes responded differently to the treatment. Comparing the treated and control groups within each sex, in other words disaggregating the data by sex and testing for effects of treatment separately in females and males, does not test whether the sexes responded differently; that is, it does not test whether the magnitude of the response differs between females and males ( Gelman and Stern, 2006 ; Makin and Orban de Xivry, 2019 ; Maney, 2016 ; Nieuwenhuis et al, 2011 ; Radke et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…There has been a recent surge of interest in characterizing aversion-resistant drinking in male and female rodents across different paradigms (Radke et al, 2021b). Although the current study is the first to characterize sex differences in footshock-resistant responding in an operant task, one study examining EtOH conditioned place preference (CPP) found that experience with a footshock on the EtOH-paired side reduced preference in male but not female mice (Xie et al, 2019).…”
Section: Discussionmentioning
confidence: 99%